2004
DOI: 10.1097/01.rli.0000124457.99229.bb
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a New Method for Quantifying In Vivo Murine Tumor Necrosis by Sonography

Abstract: In conclusion, backscattered power could be considered as a relevant parameter to quantify tumor necrosis in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 16 publications
2
15
0
Order By: Relevance
“…21 More recently, the link between the echogenecity and the degree of intra-tumoral necrosis was evaluated in a preclinical study. 22 In this study, we decided to investigate the relative antiangiogenic and antitumor properties of antiangiogenic inhibitors, using contrast-enhanced HFCDUS. We investigated and validated the potential clinical usefulness of contrast-enhanced HFCDUS/HFUS in assessing dynamically the effects of the previously studied angiogenesis inhibitors, Canstatin 14 and K1-5, 23 over a treatment period of 6 weeks, using IHC as the reference standard.…”
Section: Introductionmentioning
confidence: 99%
“…21 More recently, the link between the echogenecity and the degree of intra-tumoral necrosis was evaluated in a preclinical study. 22 In this study, we decided to investigate the relative antiangiogenic and antitumor properties of antiangiogenic inhibitors, using contrast-enhanced HFCDUS. We investigated and validated the potential clinical usefulness of contrast-enhanced HFCDUS/HFUS in assessing dynamically the effects of the previously studied angiogenesis inhibitors, Canstatin 14 and K1-5, 23 over a treatment period of 6 weeks, using IHC as the reference standard.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major advantages of DCE-US for the evaluation of new antitumor treatments is that the cost of the examination is low (70 per vial of contrast agent) and it can be repeated without adverse effects. In addition, it has been previously shown that this technique is not operator dependent (22). Recent developments, such as the use of raw linear data and perfusion and quantification software, have improved the accuracy and sensitivity of DCE-US.…”
Section: Discussionmentioning
confidence: 99%
“…24 Sunitinib induces endothelialcell apoptosis in vitro and in animal-tumour models, and pathologic changes observed suggest that dermal-vessel alteration and apoptosis might be due to direct anti-VEGFR or anti-PDGFR effects of sunitinib on dermal endothelial cells. 27 Sunitinib therapy for metastatic RCC Management strategies § for hand-foot syndrome (palmar-plantar erythrodysesthesia syndrome) include having a manicure and pedicure before treatment as a preventative measure, treatment interruptions and a shorter course (2 weeks) of therapy much more often than dose reduction. Palliative intervention includes moisturizers, foot and hand care products (e.g., gel pad inserts, cotton gloves and clobetasol propionate cream), and medication for pain management.…”
Section: Hand-foot Syndrome or Acral Erythemamentioning
confidence: 99%